Branding Strategy of the Yogyakarta City Tourism Office in Introducing Kotabaru as a Cultural Heritage Area through Event Festivals - Krisna Mulawarman; Yeni Rosilawati; Muhammad Iqbal Khatami (Poltanesa, 2026)
This research aims to analyze the marketing communication strategy implemented by the Yogyakarta City Tourism Office in promoting the Kotabaru Residential Area as both a cultural heritage site and a garden city. The research adopts a qualitative method, with data collected through desk reviews and interviews with relevant stakeholders. The findings indicate that Kotabaru’s potential tourist attractions include Dutch colonial heritage, historical events, and socio-political transformations that reflect the evolution of the city. The government has taken concrete steps to enhance the area’s appeal, including hosting various events and festivals, as well as planning infrastructure developments and promotional activities. The Yogyakarta City Government has recognized Kotabaru’s cultural and historical potential through several initiatives, including the “Kotabaru Heritage Film Festival,” “Kotabaru Ceria”, and “Kotabaru Avond Fest (Pesta Senja Kotabaru)”. These programs are designed to promote Kotabaru’s rich heritage to both local residents and visitors. In addition, infrastructure improvements such as the relocation of the electric scooter lane and the organization of the “Kotabaru Night Run” have been introduced to enhance the area’s accessibility and visitor experience. With proper management and optimization of its historical and cultural assets, Kotabaru holds strong potential to develop into a sustainable and attractive tourism destination.